2015
DOI: 10.1017/s1047951115000785
|View full text |Cite
|
Sign up to set email alerts
|

Risk for prolonged QT interval and associated outcomes in children with early restrictive eating patterns

Abstract: Mild QTc prolongation in patients with restrictive eating disorders is not related to electrolyte abnormalities or rate of weight loss in this population, suggesting that investigation about other potential risk factors of prolonged QTc interval may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…106 One study reported a nearly 10 prevalence of prolonged (.440 milliseconds) QTc interval in hospitalized adolescents and young adults with a restrictive eating disorder. 107 Repolarization abnormalities, a potential precipitant to lethal arrhythmia, 108 may prompt clinicians to also consider other factors, such as medication use or electrolyte abnormalities, that may affect cardiac conduction. 107,109 Gastrointestinal Tract Effects…”
Section: Dental And/or Oral Effectsmentioning
confidence: 99%
“…106 One study reported a nearly 10 prevalence of prolonged (.440 milliseconds) QTc interval in hospitalized adolescents and young adults with a restrictive eating disorder. 107 Repolarization abnormalities, a potential precipitant to lethal arrhythmia, 108 may prompt clinicians to also consider other factors, such as medication use or electrolyte abnormalities, that may affect cardiac conduction. 107,109 Gastrointestinal Tract Effects…”
Section: Dental And/or Oral Effectsmentioning
confidence: 99%
“…There are several studies focused on the QT interval in patients with AN and the results are inconsistent. QTc interval prolongation was observed in considerable amount of small studies [4,[14][15][16][17][18][19][20]. Majority of those study used only Bazett formula, which is highly dependent on heart rate [21].…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to examine dietary idiosyncrasies and consider specific complications of nutritional deficiencies. In a small cohort of children with avoidant鈥恟estrictive eating patterns, 10% had electrolyte abnormalities (Guerrier, Mitan, Wang, & Czosek, ) and ketogenic diets have been associated with magnesium wasting and hypomagnesemia in patients with intractable epilepsy (Kang, Chung, Kim, & Kim, ). Although this patient demonstrated a strong preference for high protein items, it is unlikely that her food preferences amounted to a sufficient ketogenic load to cause this complication.…”
Section: Discussionmentioning
confidence: 99%